Effects of Space Flight on Inflammasome Activation in the Brain of Mice - Upal Roy; Roey Hadad; Angel A. Rodriguez; Alen Saju; Deepa Roy; Mario Gil; Robert W. Keane; Ryan T. Scott; Xiao W. Mao; Juan Pablo de Rivero Vaccari (Cells)
Space flight exposes astronauts to stressors that alter the immune response, rendering them vulnerable to infections and diseases. In this study, we aimed to determine the levels of inflammasome activation in the brains of mice that were housed in the International Space Station (ISS) for 37 days. C57BL/6 mice were launched to the ISS as part of NASA’s Rodent Research 1 Mission on SpaceX-4 CRS-4 Dragon cargo spacecraft from 21 September 2014 to 25 October 2014. Dissected mouse brains from that mission were analyzed by immunoblotting of inflammasome signaling proteins and Electrochemiluminescence Immunoassay (ECLIA) for inflammatory cytokine levels. Our data indicate decreased inflammasome activation in the brains of mice that were housed in the ISS for 37 days when compared to the brains of mice that were maintained on the ground, and in mice corresponding to the baseline group that were sacrificed at the time of launching of SpaceX-4. Moreover, we did not detect any significant changes in the expression levels of the pro-inflammatory cytokines TNF-α, IL-2, IFN-γ, IL-5, IL-6, IL-12p70 and IL-10 between the ground control and the flight groups. Together, these studies suggest that spaceflight results in a decrease in the levels of innate immune signaling molecules that govern inflammasome signaling in the brain of mice.